Hubungan Motivasi Intrinsik Dengan Kinerja Perawat Di Ruang Rawat Inap Rumah Sakit Umum Wulan Windy - Sindy Syaputri Hsb; Khoirotun Najihah; Safrina Ramadhani; Nur Amalia (PT. PENERBIT TIGA MUTIARA, 2024)
Work motivation is a state or situation that cause a person to continue to improve, direct, and sustain his behavior both directly and indirectly with his work environment. This study aimed to determined the relationship of work motivation to nurse performance.This is quantitative research with a cross sectional approach, the population was 103 nurses in inpatient room and the sample was 51 nurse data collection techniques used questionnaires. The result showed that the variable of appreciation acquired (0.007), work itself (0.034) and job promotion (0.035) had a link with nursing performance. While the responsibility variable of received a value (0.891) the appreciation, work, and job promotion have a relationship with nurse performance, whereas responsibility have no relationship with nurse performance. Write an abstract content of about 250 words, covering the background of the problem, problem statements, conclusions, and the novelty of the scientific work. Abstract is only written in one paragraph.